2019
DOI: 10.1136/tobaccocontrol-2018-054841
|View full text |Cite
|
Sign up to set email alerts
|

Ban on menthol-flavoured tobacco products predicts cigarette cessation at 1 year: a population cohort study

Abstract: ObjectivesThe province of Ontario, Canada, banned the use of menthol-flavoured tobacco products as of 1 January 2017. The long-term impact of a menthol ban on smoking behaviour has not been previously evaluated.MethodsPopulation cohort study with baseline survey conducted September–December 2016 and follow-up January–August 2018 among residents of Ontario, Canada, 16 years old and over who reported current smoking (past 30 days) at baseline survey and completed follow-up (n=913) including 187 reporting smoking… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
65
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 17 publications
8
65
2
Order By: Relevance
“…Regarding smoking cessation, an Ontario menthol cigarette ban study provided the most direct results of an actual ban, with 24% of daily menthol smokers quit by one-year post-ban [17]. Another Ontario study found that all cigarette sales declined by 11%, with minimal substitution of non-menthol for menthol cigarettes [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Regarding smoking cessation, an Ontario menthol cigarette ban study provided the most direct results of an actual ban, with 24% of daily menthol smokers quit by one-year post-ban [17]. Another Ontario study found that all cigarette sales declined by 11%, with minimal substitution of non-menthol for menthol cigarettes [16].…”
Section: Discussionmentioning
confidence: 99%
“…There are also limitations related to the outcomes reported in the original studies. For example, the measure of cessation reported by Chaiton et al [17] in their study of Canada's menthol ban was a statement of "not at all" in response to being asked about their current use of menthol or non-menthol cigarettes. No results to follow-up questions about how long the individual had quit smoking or biochemical verification of cessation were reported, thereby potentially overestimating the effect of a ban.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, flavored tobacco product use is common among current tobacco‐using middle and high school students, with almost half this group using flavored smokeless tobacco (48%), menthol cigarettes (47%), flavored cigars (42%) and almost a third using flavored hookah (31%) [3]. Taken together, enforcement against e‐cigarette flavors without a restriction on all flavored tobacco products [2], including menthol products [4–6], may inadvertently provide flavored alternatives to e‐cigarettes and potentially lead to an increase in youth use of more harmful products.…”
mentioning
confidence: 99%